2020
DOI: 10.1352/1944-7558-125.6.475
|View full text |Cite
|
Sign up to set email alerts
|

Person Ability Scores as an Alternative to Norm-Referenced Scores as Outcome Measures in Studies of Neurodevelopmental Disorders

Abstract: Although norm-referenced scores are essential to the identification of disability, they possess several features which affect their sensitivity to change. Norm-referenced scores often decrease over time among people with neurodevelopmental disorders who exhibit slower-than-average increases in ability. Further, the reliability of norm-referenced scores is lower at the tails of the distribution, resulting in floor effects and increased measurement error for people with neurodevelopmental disorders. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…IRT-based latent trait scores are also associated with different standard error estimates at each point along the latent trait continuum, allowing score reliability to be estimated for each individual separately and providing more accurate score confidence intervals (CIs). Despite these and other advantages, IRT-based measurement tools are largely unused in autism research and clinical practice (though see Farmer et al, 2020). One major obstacle preventing the widespread use IRT-based scoring in these settings is that many clinicians and researchers lack the specific knowledge and expertise needed to calculate IRT-based latent trait scores from published item parameters.…”
mentioning
confidence: 99%
“…IRT-based latent trait scores are also associated with different standard error estimates at each point along the latent trait continuum, allowing score reliability to be estimated for each individual separately and providing more accurate score confidence intervals (CIs). Despite these and other advantages, IRT-based measurement tools are largely unused in autism research and clinical practice (though see Farmer et al, 2020). One major obstacle preventing the widespread use IRT-based scoring in these settings is that many clinicians and researchers lack the specific knowledge and expertise needed to calculate IRT-based latent trait scores from published item parameters.…”
mentioning
confidence: 99%
“…Similar to the SIB-R, Vineland-3 is amenable to data collection from adult caregivers and includes norm references for infants to adults with broad ability range (Fletcher, 2014). In addition, the Vineland-3 offers the ability to collect data remotely, is more amenable to collection of data from non-English speaking participants (where interpreters were able to be used), and includes person ability scores, which directly indicate changes in ability rather than relative to age-based expectations (Farmer et al, 2020). This latter scoring option addresses the limitation of standardized scores to track stabilization or improvement in a pediatric neurodegenerative process (Farmer et al, 2020;Kronenberger et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Vineland-3 offers the ability to collect data remotely, is more amenable to collection of data from non-English speaking participants (where interpreters were able to be used), and includes person ability scores, which directly indicate changes in ability rather than relative to age-based expectations (Farmer et al, 2020). This latter scoring option addresses the limitation of standardized scores to track stabilization or improvement in a pediatric neurodegenerative process (Farmer et al, 2020;Kronenberger et al, 2021). Results from this study showed that adaptive behavior scores obtained from the Vineland-3 should be considered as an outcome measure for neurodevelopmental functional assessment in CLN3, as its scores correlate strongly with UBDRS and VIQ scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations